Synthesis and Characterization of Substituted 1, 2, 4-triazole Pendant on Poly Ethylene via Microwave and Study Anticorrosion for its - Bahaa Fadhil Hamzah (Journal of Global Pharma Technology, 2019)
New derivatives of 5-substited 1, 2, 4- triazole pendant on poly ethylene were obtained through this research. Aromatic acid hydrazide derivatives were prepared from reaction of different esters (prepared from different aromatic carboxylic acid with absolute ethanol in presence of H2SO4 ) with hydrazine hydrate in presence of ethanol as a solvent then reacted with poly acrylonitrile and poly acryl amide via microwave to give (4a-e) and (5a-e) compounds respectively. All prepared compounds were characterized by physical properties as (softening point, color and conversion⁒), FT-IR, 1H-NMR for some of them and anticorrosion applications were measured.Keywords: 1, 2, 4-triazole, Microwave, Anticorrosion.